PENERAPAN NILAI KARAKTER RELIGIUS MELALUI KESENIAN REYOG PONOROGO PADA SISWA SMA MUHAMMADIYAH 1 PONOROGO - Setyarso, Pradipta Bagas; Mahardhani, Ardhana Januar; Sutrisno, Sutrisno (EDUPEDIA, 2025)
Reyog culture that we have known so far, many still consider that its activities are never free from mystical or occult activities. Reyog activities are full of occult culture and alcohol. Many reyog activists in their activities still include things that are far from religious values. Reyog art activists are still far from or less include Islamic teachings in their daily activities. The purpose of this study was to determine and analyze the process of strengthening religious character through Reyog Ponorogo Art and to analyze the factors of strengthening religious character through Reyog Ponorogo Art. This study is a qualitative descriptive study with a case study method, at Muhammadiyah 1 High School Ponorogo. Data collection techniques used observation, interviews and documentation. Data analysis techniques used reduction, data presentation and drawing conclusions/verification. The results of the study showed that the form of religious strengthening was carried out in reyog art activities through several habituation activities, namely 1). praying before and after practice or performances 2). obey, obey and carry out what the trainer says 3) perform prayers on time, 4) develop the responsibilities they carry out based on Islamic religious values. . Factors that support the strengthening of student character are: 1) Motivation from trainers and teachers, namely students are always encouraged to prioritize worship in between training 2). An appeal to respect each other between team members, manifested in the form of cooperation in the Reyog team instills values of politeness and empathy. 3). Students are taught not to be selfish and to work together in a team. in order to train emotional and ego control 4). The existence of a place of worship that supports the implementation of the obligation to carry out worship 5). Emphasis on team cohesion to foster a sense of brotherhood and comfort in the team is an important factor in strengthening character